Inflammatory Pseudotumor Complicated by Recurrent Dislocations after Revision Total Hip Arthroplasty - John Ryan Quinn; Jason Lee; Ran Schwarzkopf (Case Reports in Orthopedics)
A 71-year-old female with a history of right total hip arthroplasty presented with an enlarging pseudotumor. Pseudotumor is a known complication following metal-on-metal and metal-on-conventional polyethylene and metal-on-highly cross-linked polyethylene implants. Revision total hip arthroplasty following resection of pseudotumor has resulted in an increase in incidence of postoperative complications. Despite stable implants, these complications arise from the amount of soft tissue damage combined with the loss of tissue support around the resected hip. Our case is a clear example of a major complication, recurrent dislocation, following resection and revision surgery.